SUPERVISION AS A FORM OF PSYCHOLOGICAL MENTORING: MODERN APPROACHES AND MODELS - Конева Светлана Хамидовна (Bright Mind Publishing, 2025)
The article discusses the phenomenon of supervision as a form of professional mentoring. The historical prerequisites for the formation of supervision, its key functions, foreign and domestic approaches are highlighted. Particular attention is paid to modern models of supervision, their comparative characteristics and practical significance.